Industrialny pejzaż dźwiękowy jako przestrzeń wewnętrzna artysty w muzyce Trenta Reznora i jego zespołu Nine Inch Nasil = Industrial soundscape as the artist`s inner space in the music of Trent Reznor and his band Nine Inch Nails - Prusinowski, Piotr (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
Trent Reznor, leader and for many years the only constant member of Nine Inch Nails, has been creating music for over three decades that is generally categorised as industrial rock, but which defies clear genre classifications. As a vocalist he frequently jumps from a whisper to an angry or desperate scream and illustrates his anguished, largely autobiographical confessions with violent music which is full of tension even in the moments of introspective calm.
Keywords: rock industrialny; przestrzeń wewnętrzna; pejzaż dźwiękowy; industrial rock; inner space; soundscape